Delineamento do perfil molecular relacionado à via do receptor de fator de crescimento epitelial (EGFR) em estudo de fase I da combinação deerlotinibe e quimioirradiação em portadoras de carcinoma epidermoide do colo uterino estadiamentos IIB A IIIB - Angelica Nogueira Rodrigues (2009)
Introduction: Cervical squamous cell carcinoma represents an important public health concern in developing countries. Combined treatment involving radiotherapy and weekly cisplatin may be considered a reasonable standard of care. After the benefits obtained with the addition of platinum-based chemotherapy to radiotherapy, cure rates of locally advanced squamous cell cervical carcinoma have reached a plateau. Therapy results are sub-optimal and patients with stageIII and IVA tumors have 5 year survival rates of 40% and 15%, respectively. There is a clear need to explore new strategies to improve prognosis in this group of patients and to identify predictive biomarkers. EGFR autocrine pathway plays a crucial role in human cancer since it contributes to a number of highly relevant processes in tumor development and progression. Inhibitors of EGFR have been tested in different tumor types with promising results. Erlotinib is a drug that reversibly binds to the the EGFR tyrosine Kinase domain, thereby blocking the signal transduction events, and tumorigenic effects associated with EGFR activation. The combination of erlotinib with radiotherapy and cisplatin in locally advanced head and neck cancer showed a high complete response rate with acceptable toxicity. Purpose: To check EGFR expression and AKT/MAP phosphorylation status to outline EGFR pathway molecular profile in cervical cancer and to determine the safety and response rate of erlotinib combined tochemoradiotherapy in stage IIB to IIIB cervical cancer. Methods: EGFRexpression and AKT/MAPK phosphorylation status were determined byimmunohistochemistry in tumor tissue samples collected before treatment. In a modified Fibonacci design, the study aimed to study three cohorts of at least three patients receiving escalating doses of erlotinib(50/100/150mg) combined with cisplatin (40mg/m2, weekly, 5 cycles) and radiotherapy (external beam 4,500cGy in 25 fractions, followed by 4 fractions/600cGy/weekly of brachytherapy). Response was assessed by PET CT, MRI, CT and clinical evaluation three months after treatment end. Results: 15 patients were enrolled, 3 at dose level(DL) 50mg, 4 at DL 100mg and 8 at DL150mg. Patients presented median age 47 (36-59), stage IIB (46.2%) and IIIB (53.8%). EGFR was expressed in 90% and phosporylation of AKT and MAPK was present in 90 and 80% of the patients, respectively. Combined treatment of erlotinib and chemoradiation was well tolerated and did not increase in field or systemic toxicities. Skin rash and diarrhea were the most common adverse events, being grade 3 in 2 and 3 patients, respectively.There was no limiting in-field toxicity. 91.7% of the patients presented complete response. Conclusions: The high expression ratios of EGFR and theactivation of its major signalling routes, AKT and MAPK, create new insights to direct and indirect blocking of the EGFR pathway in cervical cancer and may be helpful, as potential biomarkers, in directing a more rationale design of future clinical trials. The high response rate and the safety of the combination support and encourage the development of a phase II trial.